2021
DOI: 10.15447/sfews.2021v19iss3art3
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Managed Flow Pulse as Food Web Support for Estuarine Habitat

Abstract: While freshwater inflow has been a major focus of resource management in estuaries, including the upper San Francisco Estuary, there is a growing interest in using focused flow actions to maximize benefits for specific regions, habitats, and species. As a test of this concept, in summer 2016, we used a managed flow pulse to target an ecologically important region: a freshwater tidal slough complex (Cache Slough Complex–CSC). Our goal was to improve estuarine habitat by increasing net flows through CSC to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In addition to a higher abundance of fishes found above the tidal excursion, SIMPER analysis indicated that high CPUE of group 5 fishes from the Aggregate was partially responsible for the differences in fish community structure identified among terminal channels. Interestingly, we did not observe a distinct seasonal pattern in community structure driven by fishes in this group, suggesting the higher abundance of mobile native fishes may actually represent individuals residing in this highly productive area year-round (Feyrer et al, 2015;Frantzich et al, 2021;Sommer et al, 2001). Further investigation is needed to test this hypothesis as to whether Yolo By-Pass productivity is retained above the tidal excursion in the Cache Slough complex and whether the fish community is truly demonstrating a bottom-up response to this productivity.…”
Section: Community Dynamics Among Terminal Channels and Excursion Zonesmentioning
confidence: 77%
“…In addition to a higher abundance of fishes found above the tidal excursion, SIMPER analysis indicated that high CPUE of group 5 fishes from the Aggregate was partially responsible for the differences in fish community structure identified among terminal channels. Interestingly, we did not observe a distinct seasonal pattern in community structure driven by fishes in this group, suggesting the higher abundance of mobile native fishes may actually represent individuals residing in this highly productive area year-round (Feyrer et al, 2015;Frantzich et al, 2021;Sommer et al, 2001). Further investigation is needed to test this hypothesis as to whether Yolo By-Pass productivity is retained above the tidal excursion in the Cache Slough complex and whether the fish community is truly demonstrating a bottom-up response to this productivity.…”
Section: Community Dynamics Among Terminal Channels and Excursion Zonesmentioning
confidence: 77%
“…Additionally, carbon sequestration in the soils of created or managed wetlands (Windham-Myers et al 2018;Wang et al 2021;Windham-Myers et al, this issue) has been proposed as a strategy to ameliorate excess CO 2 in the atmosphere globally and within the Delta. Another strategy that focuses on primary producers to mediate great accelerations is to stimulate phytoplankton blooms through managed flow pulses at times critical for recovery of endangered fishes (Williams et al 2009;Sommer et al 2020;Frantzich et al 2021).…”
Section: How Ecosystem Services and Disservices Modulate Great Accele...mentioning
confidence: 99%
“…In general, drivers of the estuarine food web are poorly understood in the Delta, leading to prominent calls for food web modeling (DISB 2021) and synthesis (Brown et al 2016). Such food web modeling would help planners anticipate how proposed wetland restoration at large scales may affect fish populations, and could aid in the design of flow actions (e.g., Frantzich et al 2021) intended to increase food resources for fish.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…This research directly evaluates whether management actions have their hypothesized outcomes. An example of this type of management-relevant science is measurement of food-web responses to a human-induced flow pulse (e.g., Frantzich et al 2021). The data used in these evaluations may be newly collected as part of the evaluation, or it may be gleaned from the estuary's rich data resource of routine monitoring programs.…”
Section: Hypothesis-driven Monitoring and Evaluation Of Management Ac...mentioning
confidence: 99%
“…Field experiments can be particularly relevant for management, but such efforts are often exceptionally difficult or impossible. Some examples of large-scale experimental field manipulations areFrantzich et al 2021;Kraus et al 2017;Sommer et al 2020a, andSommer et al 2020b, though such projects are rare because of multiple challenges, including cost, permitting, lack of infrastructure, and other logistical constraints. Enclosures, incubations, and mesocosms are therefore useful tools to generate multiple treatments and in moderately realistic conditions (e.g.,Zeug et al 2021;Strong et al 2021).…”
mentioning
confidence: 99%